2012
DOI: 10.1111/mec.12011
|View full text |Cite
|
Sign up to set email alerts
|

Genomic scan for single nucleotide polymorphisms reveals patterns of divergence and gene flow between ecologically divergent species

Abstract: Recent advances in population genomics have triggered great interest in the genomic landscape of divergence in taxa with ‘porous’ species boundaries. One important obstable of previous studies of this topic was the low genomic coverage achieved. This issue can now be overcome by the use of ‘next generation’ or short‐read DNA‐sequencing approaches capable of assaying many thousands of single nucleotide polymorphisms (SNPs) in divergent species. We have scanned the ‘porous’ genomes of Populus alba and Populus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 77 publications
(141 reference statements)
6
136
2
Order By: Relevance
“…A strong decrease of F ST on the proximal end of chromosome XIX was found, confirming previous results by Macaya-Sanz et al (2011) and Stölting et al (2013). For this specific genome region, F ST values ranged from 0.000 to 0.216 and from 0.010 to 0.549 (Table S3) (Table S3).…”
Section: Genetic Diversity and Species Differentiationsupporting
confidence: 88%
See 3 more Smart Citations
“…A strong decrease of F ST on the proximal end of chromosome XIX was found, confirming previous results by Macaya-Sanz et al (2011) and Stölting et al (2013). For this specific genome region, F ST values ranged from 0.000 to 0.216 and from 0.010 to 0.549 (Table S3) (Table S3).…”
Section: Genetic Diversity and Species Differentiationsupporting
confidence: 88%
“…In plants, resistance genes have been put forward for their potential role in the origin and maintenance of reproductive barriers through hybrid necrosis (Bomblies and Weigel 2007;Bomblies 2009). The two European Populus species, Populus alba and Populus tremula, have been described as species with incomplete reproductive barriers that hybridize despite relatively high levels of genomic divergence Lindtke et al 2012;Stölting et al 2013), largely concordant with available models of Bporous genomes^and heterogenous genomic divergence (Wu 2001;Feder et al 2012). Postzygotic selection has recently been put forward as a mechanism potentially maintaining the species barrier, but the exact selective factors acting on hybrid seedlings are currently unknown (Lindtke et al 2014).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several genomewide association, transcriptome, and population genomics studies have been reported for P. trichocarpa , contributing to the current knowledge about the species regulation of complex traits (McKown, Klápště, et al., 2014; Porth et al., 2013a, 2013b), extent of linkage disequilibrium (LD) and effective population size (Slavov et al., 2012; Zhou, Bawa, & Holliday, 2014), population structure (Geraldes et al., 2014; Slavov et al., 2012; Zhou et al., 2014), genetic diversity (Evans et al., 2014; Zhou et al., 2014), demographic history (Zhou et al., 2014), adaptation (Evans et al., 2014; Geraldes et al., 2014; Holliday, Zhou, Bawa, Zhang, & Oubida, 2016; Porth et al., 2015; Zhou et al., 2014), and sex determination (Geraldes et al., 2015). Studies in other poplar species (Stölting et al., 2013, 2015; Wang, Street, Scofield, & Ingvarsson, 2016a, 2016b) have significantly lagged behind. In fact, very limited population genetic information is available for widely distributed and ecologically and economically critical species such as Populus deltoides .…”
Section: Introductionmentioning
confidence: 99%